Lateral interbody fusion without intraoperative neuromonitoring in addition to posterior instrumented fusion in geriatric patients: A single center consecutive series of 108 surgeries - Lukas Bobinski; Per Liv; Bernhard Meyer; Sandro M. Krieg (Brain and Spine, 2023)
Introduction: Lateral lumbar interbody fusion (LLIF) and lateral thoracic interbody fusion (LTIF), supported by intraoperative neuromonitoring (IONM), gained popularity as a mini-invasive alternatives for standard interbody fusion. The objective of this study was to investigate the clinical outcome in a large elderly patient cohort who underwent LTIF/LLIF without IONM. Methods: This retrospective, single-center study enrolled elderly patients (≥70 years old) operated during the period from 2010 to 2016. Anterior lumbar interbody fusion (ALIF) in the L5/S1 segment was excluded from the analysis. Results: The study enrolled 108 patients (63 males, 58.3%) with a mean age of 76.5 ​y/o. The mean follow-up was 14.4 ​± ​11.3 months. The mean time of the surgery was 92 ​± ​34.2 ​min. The mean blood loss was 62.2 ​ml. There were no vascular or visceral surgical complications. 39 medical complications were encountered in 24 (22%) patients. Less than 5% of patients presented with a new onset of motor weakness and less than 2% of the patients developed a new sensory deficit at the discharge. 46% of patients were lost in follow-up at 12 months. Conclusions: IONM is not mandatory for LLIF/LTIF surgery in geriatric patients and has a low frequency of approach-related complications as well as neurological deterioration. Our results are comparable to the available literature. Regardless of the utilization of these mini-invasive, anterior approaches, in patients of advanced aged, the risk for major medical complications is high and is responsible for contributing to prolonged hospitalization.